2017
DOI: 10.1590/1806-9282.63.07.642
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle training protocol for stress urinary incontinence in women: A systematic review

Abstract: Summary Introduction: Strengthening exercises for pelvic floor muscles (SEPFM) are considered the first approach in the treatment of stress urinary incontinence (SUI). Nevertheless, there is no evidence about training parameters. Objective: To identify the protocol and/or most effective training parameters in the treatment of female SUI. Method: A literature research was conducted in the PubMed, Cochrane Library, PEDro, Web of Science and Lilacs databases, with publishing dates ranging from January 1992 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Several authors argue that strength training of the pelvic floor muscles is effective in the treatment of SUI in women [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors argue that strength training of the pelvic floor muscles is effective in the treatment of SUI in women [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, approximately 30% of women are unable to perform voluntary pelvic floor muscle contractions correctly despite instruction . Performance can be improved by using biofeedback to indicate when correct contractions are performed or by using electrical stimulation to improve pelvic floor muscle function and mass …”
Section: Discussionmentioning
confidence: 99%
“…PFMT can be effective at improving SUI, although more than 30% of women do not contract the muscles correctly despite instruction . Several methods to augment PFMT are available, including biofeedback, vaginal weights, and electrical stimulation …”
Section: Introductionmentioning
confidence: 99%
“…1,2 According to protocols, previous studies have recommended a 3-week-PFMT treatment frequency or more to report high cure percentual. 3,4 Oliveira et al 5 showed in a systematic review that training programs from 8 to 12 weeks seem to reduce the amount of urine leakage, and/or increase pelvic floor muscle (PFM) strength. It is emphasized that physical exercise chronic practice can be responsible for skeletal muscle adaptations, such as hypertrophy of pelvic floor (PF) area.…”
Section: Introductionmentioning
confidence: 99%